2020 CAO Clinical Practice Guideline: Optometric Low Vision Rehabilitation Executive Summary - Leat, Susan (Canadian Journal of Optometry, 2020)
The purpose of the Low Vision Clinical Practice Guideline is to assist Canadian Optometrists in the provision of the best rehabilitative care for patients with low vision. The guideline is based on current available best evidence, interpreted by an expert panel. The writing group includes optometrists from academia and private practice, representing various regions across Canada. The guideline will aid optometrists to identify patients who require low vision rehabilitation and recommends appropriate assessment and management.